An Application of the Duality Method to the Regularity of Membrane Problems with Friction (Journal of Partial Differential Equations, 1992)
Duality is applied to study the regularity of solutions to membrane problems with friction. The method consists of the characterization of the regularity of the subdifferentials of the friction functional. Then the regularity of a solution reduces to the regularity of a solution to a related elliptic boundary value problem or to that of an obstacle problem without friction.